Girish Karnad’s Hayavadana: Analysis of Text and its Theatrical Performance - Khan, Dr Amara (Journal of Research in Humanities, 2020)
I here discuss the theatrical performance of Girish Karnad’s Hayavadana (1971) with reference to the text. I have minutely observed the inclusions, extractions, replacements, erasure, and substitutions in the performance and find that this 44-minute 40-seconds theatrical performance does not include certain scenes and characters which are present in the text. For example Ganesha, Female Chorus, and the Dolls and their respective scenes are excluded for stage performance and hence make it difficult for the audience to understand the play completely. I have, therefore, focussed my discussion on the analysis of these absent characters and scenes. More specifically I have based my discussion on the use of masks in the theatrical performance as compared to their employment in Karnad’s text. Themes emphasised through masks in the text as well as in the performance are suggested in terms of Yakshagana tradition, modernity, post coloniality, and the Indian nation. I have explored how Karnad makes the traditional folk forms of Indian drama modern in their exhibition so that the local and traditional themes become suitable and effective for his present audience. The study aspires to encourage researchers fascinated in similar domains and calls attention to contemporary Indian theatre and English literature, promising inter disciplinary research